Design af active localization system front-end building blocks for MR-guided interventional procedures - Gerçek, İsmail. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
In interventional procedures imaging plays an important role, as quick and accurate determination of the interventional device position and tissue structures are crucial for the procedure. Usually interventional procedures are being conducted in X-ray fluoroscopy. However, it is highly desirable to use the MRI technology for interventional procedures, since MRI is a safe and reliable medical imaging method providing good soft tissue contrast while avoiding harmful ionizing radiation. New interventional instruments has to be designed for this purpose since there are certain constraints regarding imaging and localization process and MR physics. One such constraint is heating of conductors. MRI systems transmit received MRI signals through electrical cables. This design is effective for the conventional case, where receive coils are placed outside of the subject body. However, for the internal coils safety improvements has to be made, mainly due to the heating problem of conducting material under strong RF waves transmitted by the MRI system. To overcome the heating problem optical transmission of data and power is used. In this thesis an active localization system for catheters, which is intended to be used in interventional procedures in MRI , is studied. The purpose of the study is to design some main building blocks for such an active localization system front- end. A dickson charge pump operating with alternating input signal at 100MHz with an amplitude of 1V and generating 1.94V at its output for 100K ohm load resistance v is designed. Different receive coil sizes are studied and obtained results show Q2xR values of 1300 can be reached with the processing technology at hand. The gain stage is designed as a Low Noise Amplifier, for 64MHz and 123MHz precession frequencies. 4:112dB noise figure is obtained for LNA@64MHz and 4:813dB for LNA@123MHz.
Keywords: Magnetic resonance imaging.